Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1097/sla.0b013e3182368c4f
|View full text |Cite
|
Sign up to set email alerts
|

Selective Targeting of Genetically Engineered Mesenchymal Stem Cells to Tumor Stroma Microenvironments Using Tissue-Specific Suicide Gene Expression Suppresses Growth of Hepatocellular Carcinoma

Abstract: Exogenously added MSCs are recruited to growing HCC xenografts with concomitant activation of the CCL5 or Tie2 promoters within the MSCs. Stem cell-mediated introduction of suicide genes into the tumor followed by prodrug administration was effective for treatment of experimental HCC and thus may help fill the existing gap in bridging therapies for patients suffering from advanced HCCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 43 publications
2
88
1
2
Order By: Relevance
“…91 Indeed, MSCs introduced into the systemic circulation of tumor-bearing animals exhibit avid and preferential homing to cancerous growths, with limited homing to other tissues. 20,21 This preferential migration has now been convincingly demonstrated in a number of xenograft models, such as melanoma, 92 ovarian carcinoma, 93 breast carcinomas 21 and hepatocellular carcinomas 94 and has been described in detail using enhanced detection methods for tracking injected MSCs. 22 Importantly, endogenous MSCs have been recovered from the stroma of both experimental xenograft tumors 21 and human tumors, 6,7 suggesting that cancer development entails the continuous recruitment of MSCs, which may maintain steadystate levels within tumor stroma.…”
Section: Msc Homing To Tumorsmentioning
confidence: 99%
“…91 Indeed, MSCs introduced into the systemic circulation of tumor-bearing animals exhibit avid and preferential homing to cancerous growths, with limited homing to other tissues. 20,21 This preferential migration has now been convincingly demonstrated in a number of xenograft models, such as melanoma, 92 ovarian carcinoma, 93 breast carcinomas 21 and hepatocellular carcinomas 94 and has been described in detail using enhanced detection methods for tracking injected MSCs. 22 Importantly, endogenous MSCs have been recovered from the stroma of both experimental xenograft tumors 21 and human tumors, 6,7 suggesting that cancer development entails the continuous recruitment of MSCs, which may maintain steadystate levels within tumor stroma.…”
Section: Msc Homing To Tumorsmentioning
confidence: 99%
“…Niess et al, [252] used engineered mesenchymal stem cells (MSCs) as therapeutic vehicles for the treatment of HCC. They concluded that stem cell-mediated introduction of suicide genes into the tumor followed by pro-drug administration was effective towards liver cancer [252].…”
Section: Control Of Tumor Microenvironmentmentioning
confidence: 99%
“…They found that these vectors enabled effective elimination of human glioma xenografts while producing negligible toxic effects on normal astrocytes. Niess et al 29 used bone marrow mesenchymal stem cells (MSCs) that were modified by a suicide gene under the control of the Chemokine (C-C motif) ligand 5 (CCL5) promoter for gene therapy of hepatocellular carcinoma. They found that transplanted MSCs were recruited to the tumor site, where they differentiated and participated in tumor angiogenesis following tumor-specific activation of CCL5 promoters.…”
Section: Suicide Gene Strategiesmentioning
confidence: 99%